POWER CHARACTERISTICS OF A VIBRATOR WITH A LINEAR NONSALIENT-POLE ARMATURE MOTOR DRIVE - R.P. Bondar (National Technical University "Kharkiv Polytechnic Institute", 2014)
A vibrator with a linear reciprocating motor drive is studied. On the basis of the mathematical model developed, equations of power characteristics of the vibrator with a linear nonsalient-pole armature motor drive are obtained. Comparative calculations of the power characteristics by means of the analytical model obtained and a Simulink-model with FEM-specified parameters are carried out.